Comparison of quality properties of fresh and solar dried goji berries (Lycium Barbarum) - Ljubica Karakashova, Frosina Babanovska-Milenkovska, Jelena Mladenova, Lence Velkoska-Markovska, Viktorija Stamatovska, Namik Durmishi (ECOLOGICAL MOVEMENT OF NOVI SAD, 2022)
In this research the quality properties of fresh and solar dried goji berries (Lycium barbarum) were investigated and compared. For that purpose, freshly harvested goji berries, the JB2 variety were used. Before the drying, the berries were treated in several ways, immersion of berries in boiling water and in 1 % ascorbic acid solution; immersion of frozen berries in 1 % ascorbic acid solution; berries without treatment (control). The following parameters were analyzed in fresh and dried goji berries: the total dry matter, moisture, total acids, mineral matters (ash), glucose, fructose, vitamin C, protein, fat and total polyphenols. For that purpose, the standard laboratory methods were used. Sensory properties were estimated by scoring method (max. 20).
Keywords: goji berries, solar dryer, quality and sensory properties